Níveis de inclusão de farelo de mamona detoxificado na ensilagem de cana de açúcar na dieta de ovinos: desempenho e parâmetros histológicos - Dantas Junior, Paulo Rodrigues (2020)
The objective of the present study was to evaluate the histological organ changes of the digestive system and kidney of sheep submitted to levels of inclusion of castor meal in sugarcane silage. Forty (40) Santa Inês crossbred sheep, with average live weight of 20 kg, were submitted to an adaptation period of 14 days and 60 days of experimental period (totaling 74 days of confinement). The treatments were constituted as follows: S0 - sugarcane silage (control); S5 - sugarcane silage + 5% of castor bean meal in cane natural matter (MN); S10 - sugarcane silage + 10% of castor meal in sugarcane MN; S15 - sugarcane silage + 15% of castor meal in sugarcane MN; S20 - sugarcane silage + 20% of castor meal in sugarcane MN. To do the histopathological and histomorphometric analyzes, fragments no larger than 0.5 cm3 of the organs: liver and kidney were sectioned, and fragments no larger than 1 cm of the organs: rumen and small intestine. The samples were visualized in a microscope coupled to a digital camera, with the aid of imaging software. In the rumen, muscle layer thickness, papilla height, papilla width and epithelium thickness were significantly influenced (P <0.05) by the inclusion of castor meal in sheep feed. The thickness of the keratinized portion of the epithelium had no significant effect (P> 0.05) on the inclusion of castor meal in the sheep diet. The inclusion of castor meal in sheep feed significantly influenced (P <0.05) the size of the submucosa, crypt, villus, mucosa, villus / crypt ratio and number of goblet cells in the intestine. Dry matter consumption and average weight gain grow linearly as it includes castor meal in the animals' diets. Regarding glycogen storage, it was observed that there was a significant difference (P <0.05) with the inclusion of castor meal. It was concluded that the use of castor meal offered to Santa Ines sheep during 74 days of confinement changes the ruminal, intestinal morphology, performance and the glycogen stock.